Systematic Review and Meta-Analysis of Correlation of Progression-Free Survival-2 and Overall Survival in Solid Tumors - Chowdhury, Simon; Mainwaring, Paul; Zhang, Liangcai; Mundle, Suneel; Pollozi, Eneida; Gray, Alexander; Wildgust, Mark (Frontiers in Oncology, 2020)
Background: Using progression-free survival (PFS)2, time from randomization to 2nd disease progression or death, is proposed as a surrogate for overall survival (OS) in oncology clinical trials. We used published data from solid tumor trials to assess whether PFS2 and OS are correlated. Methods: A literature search identified studies that reported PFS, PFS2, and OS. Two reviewers screened for eligibility, and documented PFS2, PFS or time from 1st to 2nd disease progression or death and OS. Correlation between PFS2 and OS was assessed using: (1) Kendall's Tau + Pearson's correlation coefficient in randomized controlled trials (RCTs); (2) Meta-analysis with the random effects model to compute the pooled correlation of PFS2 and OS. Results: Overall, 133 studies met search criteria, 15 (28 arms) had complete PFS2 and OS data in ovarian, gastric, colorectal, prostate, lung, renal and breast cancers. A positive correlation for PFS2 and OS was found for all 15 studies (Kendall's Tau = 0.7 [95% CIs 0.54, 0.78]); 10 RCTs (Pearson's correlation coefficient = 0.86); and meta-analysis from 7 trials (pooled Spearman's correlation coefficient = 0.84 [p = 0.0001; 95% CIs 0.71, 0.96]). Conclusions: In this retrospective analysis PFS2 strongly correlates with OS supporting the use of PFS2 to measure long-term clinical benefit when OS cannot be assessed.